Applying modern technologies in the middle stage and their impact on students 'learning from the teachers' point of view (Journal of the College of Basic Education, 2022)
The research aims to know (the application of modern technologies in the middle stage and their impact on students 'learning from the teachers' point of view) and is achieved through the following question: -1- Exposing the reality of using modern technologies in middle and high schools from the teachers' point of view.2- Identifying the most prominent obstacles that prevent the use of modern technologies from the teachers' point of view.The researcher adopted the analytical descriptive approach and the sample was represented by middle and high school teachers, and the following statistical methods were used to show the results and from these means (Cooper's agreement equation, Varkronbach equation, measurement of stability coefficient) and the results were shown as follows1- The teacher’s employment rates for educational technologies in the educational process, which the researcher selected, were weak.2- The most severe difficulties revealed by the teachers was the lack of training courses for teachers on the production and development of educational materials, as their percentage reached (87%). The least of these difficulties is the student’s lack of acceptance of the teaching aids, as it reached (3.3%)